The Role of Work Motivation in Linking Compensation and Non-Physical Work Environment to Employee Performance at PT Muawanah Al-Ma’soem - Dwi Utari, Anggita; Hermina, Nurul (Dinasti Publisher, 2026)
This study analyzes the effect of compensation and the non-physical work environment on employee performance with work motivation as a mediating variable at PT. Muawanah Al-Ma’soem. This research addresses the need to understand how financial and non-financial factors simultaneously influence employee performance through psychological mechanisms. A quantitive method was employed using survey data collected from 98 employees. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings reveal that compensation and the non-physical work environment have positive and significant effects on employee performance. Work motivation also has a significant positive effect on employee performance and acts as a mediating variable in the relationship between compensation, the non-physical work environment, and employee performance. The theoretical contribution of this study lies in strengthening and extending motivational theory by empirically validating the mediating role of work motivation in linking compensation and non-physical work environment factors to employee performance. Practically, the result suggest that organizations should integrate fair compensation policies and supportive workplace relationships to improve employee performance sustainably.